2013
DOI: 10.3390/s131013575
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Carbide-Based Hydrogen Gas Sensors for High-Temperature Applications

Abstract: We investigated SiC-based hydrogen gas sensors with metal-insulator-semiconductor (MIS) structure for high temperature process monitoring and leak detection applications in fields such as the automotive, chemical and petroleum industries. In this work, a thin tantalum oxide (Ta2O5) layer was exploited with the purpose of sensitivity improvement, because tantalum oxide has good stability at high temperature with high permeability for hydrogen gas. Silicon carbide (SiC) was used as a substrate for high-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Starting from the standard capacitor structure: catalytic metal gate-silicon dioxide-silicon carbide (MOSiC) [10], the technological processes were continually adjusted for better-quality structures, notable progress in sensing qualities being reported [11][12][13]. Despite their well-known drawbacks, the most used catalytic gate metal remains Pd [8] and Pt [14], while the most research effort is concentrated on the improving the oxide characteristics. Therefore, in order to increase the sensitivity, alternative insulator layers replacing SiO 2 (i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Starting from the standard capacitor structure: catalytic metal gate-silicon dioxide-silicon carbide (MOSiC) [10], the technological processes were continually adjusted for better-quality structures, notable progress in sensing qualities being reported [11][12][13]. Despite their well-known drawbacks, the most used catalytic gate metal remains Pd [8] and Pt [14], while the most research effort is concentrated on the improving the oxide characteristics. Therefore, in order to increase the sensitivity, alternative insulator layers replacing SiO 2 (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Standard semiconductor devices, including metal oxide semiconductor (MOS) capacitors, Schottky diodes and field effect transistors, firstly fabricated on Si technology, are also developed on SiC technology and explored for hydrogen sensing, showing attributes that make them far superior to Si for harsh environments [4][5][6][7][8]. Although proposed and developed several decades ago, in the 70s, the MOS devices are still one of the primary sensing platforms fabricated firstly on silicon [9] and later on, in 1993, on SiC [10].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor-based gas sensors have the benefits of low cost, small size, and low power consumption. Various semiconductor materials have been utilized to implement hydrogen sensors [4][5][6][7][8][9][10], among which GaN is an attractive material for a hydrogen sensor operating at high temperatures because of its wide energy bandgap with low intrinsic carrier density [11][12][13]. The low intrinsic carrier density allows GaN to maintain its semiconductor properties in high-temperature environments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the wide band gap, a high-breakdown electric field, fast response time, mechanical strength and a low leakage current of SiC made it a better material than silicon in hightemperature electronic applications. [4][5][6][7][8] In addition, the semiconductor coating layers such as SiC and Si have features apart from sensitivity enhancement of the optical fiber, such as fiber protection, tunability of the resonance wavelength region and bio-chemical compatibility of the sensor. 9,10 According to a study reported by Kumar et al, 3 the performance of an optical fiber sensor fabricated using surface plasmon resonance (SPR) technique can be enhanced by using silicon carbide (SiC).…”
Section: Introductionmentioning
confidence: 99%